1989
DOI: 10.1104/pp.89.4.1066
|View full text |Cite
|
Sign up to set email alerts
|

Mild Water Stress of Phaseolus vulgaris Plants Leads to Reduced Starch Synthesis and Extractable Sucrose Phosphate Synthase Activity

Abstract: Mild water stress, on the order of -1.0 megapascals xylem water potential, can reduce the rate of photosynthesis and eliminate the inhibition of photosynthesis caused by 02 in waterstress-sensitive plants such as Phaseolus vulgaris. To investigate the lack of 02 inhibition of photosynthesis, we measured stromal and cytosolic fructose-1,6-bisphosphatase, sucrose phosphate synthase, and partitioning of newly fixed carbon between starch and sucrose before, during, and after mild water stress. The extractable acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 26 publications
4
91
0
5
Order By: Relevance
“…Numerous reports have described decreased activity of sucrose-phosphate synthase (SPS), a key enzyme in sucrose synthesis, in plant leaves during drought [79][80][81]. Similar trends have been observed in our study, including the downregulation of SPS mRNA and decreased sucrose content.…”
Section: Effects Of Drought On Carbohydrate Fatty Acids and Amino Asupporting
confidence: 78%
“…Numerous reports have described decreased activity of sucrose-phosphate synthase (SPS), a key enzyme in sucrose synthesis, in plant leaves during drought [79][80][81]. Similar trends have been observed in our study, including the downregulation of SPS mRNA and decreased sucrose content.…”
Section: Effects Of Drought On Carbohydrate Fatty Acids and Amino Asupporting
confidence: 78%
“…Only 8% to 10% of the newly fixed 14 C is partitioned to starch in poplar (Populus spp. ; Dickson and Larson, 1981) and apple (Cheng et al, 2005), whereas this figure is more than 30% in garden bean (Phaseolus vulgaris; Vassey and Sharkey, 1989), potato (Solanum tuberosum; Rung et al, 2004), and Arabidopsis (Sun et al, 1999). Apparently, the synthesis of transport sugars in passive loading plants diverts carbon away from starch synthesis and provides a pool of soluble carbohydrate for use in metabolism and export at night.…”
Section: Discussionmentioning
confidence: 87%
“…Flexas and Medrano, 2002;Flexas et al, 2004). Metabolic adjustments can take many forms, and may include the reduction of enzyme activity necessary for RuBP regeneration , reduced nitrate reductase activity (as an indicator of nitrate utilisation) (Smirnoff and Stewart, 1985), and the reduction of sucrose phosphate synthase (Vassey and Sharkey, 1989). It has been suggested that all of these responses can play some role in the control of photosynthesis (Loreto and Centritto, 2008), depending on the degree of water stress encountered and the relevant time scales involved.…”
Section: Discussionmentioning
confidence: 99%